1999
DOI: 10.1007/pl00007062
|View full text |Cite
|
Sign up to set email alerts
|

Routes of Ethephon Uptake in Pineapple (Ananas comosus) and Reasons for Failure of Flower Induction

Abstract: Ethylene-releasing agents such as ethephon (2-chloroethylphosphonic acid) are used widely to induce flowering in pineapples (Ananas comosus (L.) Merrill). However, ethephon treatment is less reliable in summer, particularly if plants are treated on abnormally hot days. [(14)C]ethephon was used to follow uptake and translocation in leaf tissues. Up to 30% of the ethephon entered the leaf within 4 h, and up to 60% by 24 h. Uptake was dramatically modified by temperature, relative humidity, solution pH, and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Recent work demonstrated the uncoupling effect of CMNP, and a link between cellular energy shortage, lipid signaling and citrus abscission was suggested (Alferez et al 2005). Ethephon is an agrochemical used to advance ethylene-related processes such as abscission in cherries and flowering in pineapple (Bukovac et al 1969, Turnbull et al 1999. Ethephon uptake into plant tissue results in cleavage of the molecule to yield ethylene, but hydrochloric acid and phosphate are also released (Warner and Leopold 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work demonstrated the uncoupling effect of CMNP, and a link between cellular energy shortage, lipid signaling and citrus abscission was suggested (Alferez et al 2005). Ethephon is an agrochemical used to advance ethylene-related processes such as abscission in cherries and flowering in pineapple (Bukovac et al 1969, Turnbull et al 1999. Ethephon uptake into plant tissue results in cleavage of the molecule to yield ethylene, but hydrochloric acid and phosphate are also released (Warner and Leopold 1969).…”
Section: Discussionmentioning
confidence: 99%
“…In weed seed germination studies only a small portion of 14 Clabeled ethephon was released as ethylene [45]. Others have also shown low and inconsistent ethephon conversion efficiency [46] [49]. Thus, the application of ethephon may not always mimic ethylene treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Plants need oxygen for respiration and energy release. CO 2 fixation is limited by environmental stresses, such as cold and high temperature, drought, and salt stress which reduce NADP + regeneration and thus induce accumulation of ROS including hydrogen peroxide (H 2 O 2 ), superoxide radical (O 2− ), and hydroxyl radicals (OH − ) in leaves [45] [46]. Previous cotton research showed that premature leaf senescence, reflected as aggregated membrane damage, lipid peroxidation, and decreased photosynthesis, is a result of imbalance of ROS metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In order to appear on the market on time, flowering-inducing agents, such as ethylene and its analogue, were used for the cultivation of bromeliads. The rosulated leaf of bromeliads can filtrate the water and nutrition, and the scalelike hairs on the leaf base epidermis can absorb water, nutrition and ethylene (Turnbull et al, 1999). Exogenous ethylene and its analogue might induce bromeliads flower by increasing endogenous ethylene.…”
Section: Introductionmentioning
confidence: 99%